Epidemiology of human avian influenza in Indonesia, 2005-2009: a descriptive analysis (Medical Journal of Indonesia, 2010)
Aim The study set out to better understand the epidemiology, natural history, therapeutic management and outcomes associated with confirmed human cases of Avian Influenza (AI) in Indonesia. Methods This observational study utilized data from 93 cases with laboratory-confirmed H5N1 Influenza between September 2005 and August 2009. Cases were identified through records obtained from the Ministry of Health, as well as the Provincial health office and district health office records. Categorical data were analyzed with frequency tables, chi-square tests, and relative risks, and continuous data were analyzed using univariate statistics and Wilcoxon tests. Results Most subjects (54%) first presented to a physician’s office or clinic. All of the subjects were hospitalized, and the vast majority (85%) had respiratory symptoms as their predominant symptom at presentation. There was no clear association of any of these case characteristics with survival. Cases with direct poultry exposure were 2.8 times more likely to receive oseltamivir treatment than those without direct exposure (RR = 2.89, 95% CI 1.44 – 5.78). While the overall number of survivors was small, cases with documented oseltamivir treatment were approximately 24% more likely to survive than cases for which oseltamivir treatment was not documented (RR 1.24; 95% CI: 0.34-4.58). In oseltamivir treated cases, the median time from symptom onset to start of antiviral treatment was 2.5 days in survivors compared to 7.0 days for those who died. Fatality, therefore, may be related to delay in initiation of treatment after presentation. Conclusions The data suggest that early treatment with the antiviral drug oseltamivir may play an important role in survival. However, a low clinical suspicion of disease likely remains an important impediment to early diagnosis. Therefore, a clear policy for the protocol of early diagnosis & treatment of febrile illness including influenza is necessary. (Med J Indones 2010; 19:64-70) Keywords: human avian influenza, antiviral drugs, oseltamivir, survival, Indonesia